Anaemia in Post-Menopausal Women-A Hidden Hunger - Shah, Syed Umer; Hafeez, Muhammad; Naveed, Muhammad; Hussain, Altaf; Khan, Muhammad Shahid; Shahbaz, Shanzah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the factors of iron deficiency anaemia among the post-menopausal women in our population. Study Design: Cross-sectional study. Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Aug 2019 to Jan 2020. Methodology: A total of 300 post-menopausal women were included in this study. Menopausal status was taken as one year after the last menstrual period. Iron deficiency anaemia was diagnosed, based on haemoglobin and ferritin levels. In addition,the relationship of age, age at menopause, comorbid medical illnesses and duration of menopause was assessed with the presence of iron deficiency anaemia among the post-menopausal women participating in this study. Results: Out of 300 post-menopausal women studied in the given period, 124(41.3%) had no anaemia, while 176(58.7%) had the iron deficiency anaemia. Furthermore, 225(75.0%) had menopause after the age of forty, while 75(25.0%) had menopause after the age of forty. After applying the binary logistic regression analysis, we found that advancing age, longer duration since menopause and presence of medical comorbidities had a statistically significant association with anaemia in the target population. Conclusion: This study showed a high frequency of iron deficiency anaemia among post-menopausal women. In addition, women with longer duration since menopause, advanced age and other medical illnesses were more at risk of having iron deficiency anaemia s compared to other women.